2020
DOI: 10.3389/fgene.2019.01348
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA RAET1K Enhances CCNE1 Expression and Cell Cycle Arrest of Lung Adenocarcinoma Cell by Sponging miRNA-135a-5p

Abstract: Molecular dysregulation is believed to participate in the onset and progression of lung adenocarcinoma (LUAD). This study aimed to identify and evaluate the potential key long noncoding RNAs (lncRNAs) involved in the significant dysfunctional process of LUAD. We found that lncRNA retinoic acid early transcript 1K (RAET1K) was upregulated in tumor tissues and were correlated with a poor prognosis of patients with LUAD; further, for the first time, we detected the biological roles of RAET1K. Weighted gene correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…For example, downregulation of RAET1K blocks the cell cycle arrest of lung adenocarcinoma cells through sponging miR-133a-5p to downregulate its level, and overexpression and miR-135a-5p exhibits an opposite effect of RAET1K knockdown. 11 In our study, we found that miR-503-5p was downregulated in bone marrow samples of AML patients and two cell lines, and an obviously negative correlation between RAET1K and miR-503-5p level in bone marrow tissues of AML patients was observed. Hence, we speculated miR-503-5p might be a target of RAET1K and the function of RAET1K in AML might be mediated by miR-503-5p.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…For example, downregulation of RAET1K blocks the cell cycle arrest of lung adenocarcinoma cells through sponging miR-133a-5p to downregulate its level, and overexpression and miR-135a-5p exhibits an opposite effect of RAET1K knockdown. 11 In our study, we found that miR-503-5p was downregulated in bone marrow samples of AML patients and two cell lines, and an obviously negative correlation between RAET1K and miR-503-5p level in bone marrow tissues of AML patients was observed. Hence, we speculated miR-503-5p might be a target of RAET1K and the function of RAET1K in AML might be mediated by miR-503-5p.…”
Section: Discussionsupporting
confidence: 47%
“… 30 High levels of SNHG3 predict a poor outcome for AML, and downregulation of SNHG3 has been identified to effectively suppress cell growth of AML cells. 31 RAET1K has been only studied in hepatocellular carcinoma, 10 and lung adenocarcinoma, 11 so we explored the potential role of RAET1K in AML. Interestingly, our study revealed a function of RAET1K in AML and provided that RAET1K might be a novel diagnostic and therapeutic target for AML, which even might contribute to identify and develop new anti-cancer agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of RAET1K in two tumoural cell lines, A549 and H1299, repressed CCDE1 expression and thus hindered cell cycle progression from the G1 to the S phase. Thus, RAEK1K is considered as a repressor of cell arrest mediated by RA [ 120 ].…”
Section: Role Of Lncrnas In An Ra-mediated Diseasesmentioning
confidence: 99%
“…The upregulation of miR-135a promotes cell apoptosis and inflammation, along with inhibited cell proliferation and decreased macrophage autophagy [15]. Furthermore, miR-135a participates in the regulation of cyclin E1 (CCNE1) expression and the accumulation of cells arrested at the G1/S phase boundary [16]. In addition, hsa-miR-135 is associated with the survival of patients who have serous ovarian carcinoma, and thus may serve as a potential prognostic biomarker [17].…”
Section: Introductionmentioning
confidence: 99%